Diseño y construcción de un banco de pruebas para análisis de variables eléctricas en el arranque de motores. - Chiliquinga Chanaluisa, Elber Dario (2023)
The difficulty of visualizing electrical variables (voltage and current), and the behavior of the starting current in three-phase motors has generated a gap between theory and practice. For this reason, this technological project presents the design and construction of a test bench through a data acquisition system that allows obtaining key variables such as voltage and current, during motor starting and also visualizing the starting curve in real time. For this, a system of electrical protections, conductors, thermal relays, contactors was implemented taking into account the NEC regulations that must be modeled for specific loads. For the case study, there are 8 three-phase electric motors (five 1 HP motors, one 1/2 HP motor and one 2 HP motor) that work at 220 V, each study situation will be respectively with the use of a s7 PLC. -1200 through a MODBUS TCP-IP communication to the SENTRON PAC, for communication to LabVIEW through an OPC server, in this way the creation of a graphical interface is carried out, which allows the visualization of electrical parameters and starting currents. When analyzing the results of a 2 Hp three-phase motor, using the three types of starting proposed, it is seen that the maximum no-load starting curve is 9.57 A and when a load is applied, the current increases to 17.27 A, through tests. With star delta starting, a lower delta current was obtained, which is 4.60 A and stabilizes at its working current of 2.48 A. For starting with a frequency converter, a maximum current of 4.61 A was obtained and stabilizes at its working current of 4.2 A, with these last two types of starts applied it is possible to avoid starting current peaks and thus improve the useful life of the motor, complying with the NEC regulations for the system in electrical installations in the applied inductive loads.